Effect of small addition of aluminium on electrochemical corrosion behaviour of magnesium-calcium sacrificial anode in underground environment - Shaiful Rizam, Shamsudin; G., Sasirehka; A. M. H., Firdaus; C. I., Mahdi; D. M., Nazree; A. R., Daud; A. A., Azrem (PETRONAS, 2010)
Malaysia International NDT “Non Destructive Testing” Conference and Exhibition ‘09 (MINDTCE ’09), 20th - 21st of July 2009 was held in Kuala Lumpur. Organized by PETRONAS, ASCOPE GAS Centre, MSNT, SIRIM and Nuclear Malaysia.